PENGEMBANGAN KOMPETENSI PROFESI PROGRAM STUDI KOMUNIKASI DAN PENYIARAN ISLAM - Zainul Abas (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2017)
This research is focused on the development of science profession course in the Program of Communication Studies and Islamic Broadcasting since when it became a part of the Department of Da’wah, STAIN Surakarta, to becoming part of the Da’wah and Communication Major, Faculty of Ushuluddin and Da’wah, IAIN Surakarta. Some problems in this research are: (1) How does the distribution map of the existing profession in the Major of Communication and Islamic Broadcasting (KPI)? (2) How does the development of profession-based courses in the Major of Communication and Islamic Broadcasting (KPI)? Researchers categorize that the distribution map of subjects in KPI Major into six components, namely component Institute, component Department, Component Science Courses of KPI Major, Professional Components of KPI Major in Journalism Concentration, Professional Components of KPI Major in Broadcasting Concentration, Professional Components of KPI Major in Public Relation Concentration. With such a profession component in KPI Major, it can be expected to create students for becoming professionals in their field with the result by targeting appropriate academic skills in learning outcomes and the standards graduates competency will be achieved.